Understanding the relationship between perceived discrimination and mortality in United States adults. (1st February 2023) - Obaoye, Joanna O.; Dawson, Aprill Z.; Thakkar, Madhuli; Williams, Joni S.; Egede, Leonard E.
Abstract: Objective: To understand the relationship between mortality and three types of perceived discrimination (lifetime, daily, chronic job) using a nationally representative sample of U.S. adults. Methods: Data from 4562 adults in the Midlife in the United States (MIDUS) between 2004 and 2006 (MIDUS II and MIDUS African American sample) were analyzed. Unadjusted associations between primary independent discrimination variables (lifetime, chronic job, daily) and mortality were analyzed using univariate Cox's proportional hazards regression models. Covariates were added to the models by group: predisposing (sex, age, race/ethnicity, education, marital status); enabling (household income, employment status, insurance status); and need factors (body mass index, diabetes, hypertension, stroke, cancer) to estimate hazard ratios. Results: After adjusting for all covariates, hazard ratios for lifetime discrimination (HR: 1.09, p = 0.034) and daily discrimination (HR: 1.03, p = 0.030) were statistically significant. There was no relationship between mortality and chronic job discrimination (HR:1.03, p = 0.15). Conclusions: Adults experiencing lifetime and daily discrimination had significantly increased risk of mortality after adjusting for predisposing, enabling, and need factors. The findings highlight the importance of screening patients during clinical encounters for experiences of discrimination and providing appropriate resources to mitigate the negative impact of discriminatory events on mortality. Future research should work to fully understand the mechanism by which discrimination increases risk of mortality. These future findings should be used to develop targets for interventions designed to decrease mortality among adults who have experienced discrimination.